2021
DOI: 10.1002/hbm.25361
|View full text |Cite
|
Sign up to set email alerts
|

Brain gray matter structures associated with trait impulsivity: A systematic review and voxel‐based meta‐analysis

Abstract: Trait impulsivity is a multifaceted personality characteristic that contributes to maladaptive life outcomes. Although a growing body of neuroimaging studies have investigated the structural correlates of trait impulsivity, the findings remain highly inconsistent and heterogeneous. Herein, we performed a systematic review to depict an integrated delineation of gray matter (GM) substrates of trait impulsivity and a meta‐analysis to examine concurrence across previous whole‐brain voxel‐based morphometry studies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
32
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 166 publications
(243 reference statements)
8
32
0
Order By: Relevance
“…Boys relative to girls showed higher impulsivity in all dimensions, consistent with the previous studies of a variety of different impulsivity measures in both children and adults (Cross, Copping, & Campbell, 2011; Pan et al, 2021; Van der Linden et al, 2006). Girls and boys also demonstrated differences in the volumetric correlates; for instance, boys vs. girls showed higher left anterior insula GMV in association with lack of premeditation; in contrast, girls vs. boys showed higher bilateral anterior insula GMVs in association with sensation seeking.…”
Section: Discussionsupporting
confidence: 89%
“…Boys relative to girls showed higher impulsivity in all dimensions, consistent with the previous studies of a variety of different impulsivity measures in both children and adults (Cross, Copping, & Campbell, 2011; Pan et al, 2021; Van der Linden et al, 2006). Girls and boys also demonstrated differences in the volumetric correlates; for instance, boys vs. girls showed higher left anterior insula GMV in association with lack of premeditation; in contrast, girls vs. boys showed higher bilateral anterior insula GMVs in association with sensation seeking.…”
Section: Discussionsupporting
confidence: 89%
“…Meanwhile, increased FC between the putamen and the MTG/STG and decreased FC between the putamen and cerebellum posterior lobe were also presented in the current analysis. The STG/MTG is a crucial component of the perceptual system involved in facial emotion processing, social threat evaluation [69], analysis of the dispositions and intentions of others' actions [70,71], visual perception and mental imagery [72], and integration of interoceptive information with information about the current environmental situation [73], all of which may be related to SAD characteristics such as excessive focus on others' intentions and facial expressions, excessive fear for negative evaluation and scrutiny by others [74], and increased saliency of the social situations when SAD patients envision themselves in hypothetical scenes [75]. Interestingly, a recent study also reported increased intrinsic rs-FC in the left MTG in families genetically enriched for SAD, indicating the crucial roles of the MTG as a network hub in the socially anxious brain [76].…”
Section: Cortico-striato-cerebellar Circuitry In Sadmentioning
confidence: 99%
“…The frontal-parietal-temporal and subcortical ICs were the primary components that we hypothesized to associate with both diet and disinhibition. In fact, IC1 was the only brain component associated with disinhibited behavior, the positive association indicating that higher volumes in the frontal-temporal/parietal areas were associated with higher disinhibition scores, which was surprising as we had expected overall lower brain volumes to relate to disinhibition based on previous literature [ 37 , 38 ]. IC1 (frontal-parietal-temporal volume) was also the brain component most strongly associated with all dietary components except the restricted diet.…”
Section: Discussionmentioning
confidence: 80%
“…Specifically, differences in the cortical-striatal pathways associated with cognitive control have been associated with high levels of disinhibited behavior. Both subcortical volumes of the striatum and frontal cortical thickness have been found to be decreased in association with disinhibition [ 37 , 38 ]. Functionally, frontal-parietal and striatal hypoactivation has been found in impulsive subjects during inhibition tasks [ 31 , 39 , 40 , 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%